2017
DOI: 10.1111/are.13341
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary inulin and Jerusalem artichoke (Helianthus tuberosus) tuber on the growth performance, haematological, blood chemical and immune parameters of Nile tilapia (Oreochromis niloticus) fingerlings

Abstract: This study investigated the effects of dietary inulin or Jerusalem artichoke (JA) on the growth performance, haematological, blood chemical and immune parameters of Nile tilapia fingerlings. Five treatment diets were designed to incorporate inulin at 0 (basal diet), 2.5 and 5.0 g/kg and JA at 5.0 and 10.0 g/kg. Two basal diets including fish meal and formulated experimental feed were used for fry and fingerling growing periods, respectively. During the fry growing period, larvae were fed treatment diets for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
2
20
1
Order By: Relevance
“…() did not observe any differences in protein, fat and moisture of Asian seabass fed with different levels of dietary MOS after 60 days. Moreover, similar results have been reported in the other studies on some fishes such as hybrid striped bass ( Morone chrysops × Morone saxatilis ) (Burr, Hume, Ricke, Nisbet, & Gatlin, ), red drum ( Sciaenops ocellatus ) (Buentello, Neill, & Gatlin, ), gilthead seabream ( Sparus aurata ) (Dimitroglou et al., ; Gültepe, Salnur, Hoşsu, & Hisar, ), European sea bass ( Dicentrarchus labrax ) (Torrecillas et al., , ) and Nile tilapia ( Oreochromis niloticus ) (Tiengtam, Paengkoum, Sirivoharn, Phonsiri, & Boonanuntanasarn, ). In contrast to this result, the elevated carcass protein was reported in Atlantic salmon ( Salmo salar ) and Asian seabass treated with dietary MOS and inulin (Ali, Ambasankar, Nandakumar, Praveena, & Syamadayal, ; Grisdale‐Helland, Helland, & Gatlin, ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…() did not observe any differences in protein, fat and moisture of Asian seabass fed with different levels of dietary MOS after 60 days. Moreover, similar results have been reported in the other studies on some fishes such as hybrid striped bass ( Morone chrysops × Morone saxatilis ) (Burr, Hume, Ricke, Nisbet, & Gatlin, ), red drum ( Sciaenops ocellatus ) (Buentello, Neill, & Gatlin, ), gilthead seabream ( Sparus aurata ) (Dimitroglou et al., ; Gültepe, Salnur, Hoşsu, & Hisar, ), European sea bass ( Dicentrarchus labrax ) (Torrecillas et al., , ) and Nile tilapia ( Oreochromis niloticus ) (Tiengtam, Paengkoum, Sirivoharn, Phonsiri, & Boonanuntanasarn, ). In contrast to this result, the elevated carcass protein was reported in Atlantic salmon ( Salmo salar ) and Asian seabass treated with dietary MOS and inulin (Ali, Ambasankar, Nandakumar, Praveena, & Syamadayal, ; Grisdale‐Helland, Helland, & Gatlin, ).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Li et al (2008) and Ali et al (2017a) showed that dietary 0.4 g/kg XOS and 2.5-10 g/kg FOS could increase serum complement and lysozyme activity of turbot and lysozyme activity of Asian seabass, respectively. In the present study, alternative complement activity in fish fed on 5 and 10g/kg XOS were significantly higher and lower compared to the control fish; nonetheless, the amounts of total immunoglobulin and lysozyme activity were not affected by dietary XOS, even though the amounts of these factors in the control group were slightly lower than those of XOS Hoseinifar, Merrifield, Barati, & Abadi, 2012;Tiengtam et al, 2017), inulin in gilthead seabream (Cerezuela, Cuesta, Meseguer, & Esteban, 2008) and MOS in European sea bass (Torrecillas et al, 2007), respectively.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The tilapia group is the second most produced fish worldwide, after the carps (FAO, 2018), and its production is expected to further increase to reach the global food demand (Tiengtam et al, 2017). Nile tilapia, Oreochormis niloticus , is the target species of this study; it presents highly favourable characteristics for aquaculture, such as fast growth in high densities, hardiness, easy reproduction and high market acceptance (Watanabe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%